Critical Success Factors in Teaching Strategic Sales Management: Evidence From Client-Based Classroom and Web-Based Formats. Issue 3 (1st September 2016) - Jaskari, Harri; Jaskari, Minna-Maarit
Abstract : The importance of sales management as an interface between a company and its customers is widely recognized. However, the teaching of strategic sales management has not received enough attention in marketing education literature. This study analyzes an experiential client-based method for teaching a strategic sales management course. The authors first discuss experiential and client-based pedagogies in sales learning. Second, the authors describe the course, case method, and two different formats. Third, the authors compare the learning outcomes and identify 5 critical success factors that teachers need to consider. The authors conclude by suggesting to sales educators ways to overcome these challenges.